Investigating the Partial Replacement of Crushed Run Rock with Reclaimed Asphalt Pavement in Base Course. - Ninyesiga, Bruno (Kabale University, 2025)
Overlay and maintenance resolve medium distress, but reconstruction may be feasible and economical while Asphalt pavement is badly deteriorated with time and traffic. This requires the removal of existing pavement surfaces. Recycling such construction waste has benefited from an economic to sustainability point of view and reduces the exploitation of natural resources. The shortage of virgin aggregate supplies along with the increase in processing and hauling costs has encouraged the use of reclaimed material from the old structure as base course construction materials, and involved in regular practice in various countries around the world. However, RAP materials may not be conventional road-making materials and need improvement. This study aimed to investigate the Engineering properties effect of using RAPs and CRR in their natural state by conducting common laboratory tests in the first phase, and Second phase of the study was intended to analyze the strength and interpret the optimum allowable percentage as partial replacement of CRR blended with 10/90, 20/80, 30/70, 40/60, 50/50 proportions by total weights for RAP as compared results with the general specification for base course materials. According to the general specification, the natural blends of RAP-CRR were classified. The mechanical and physical properties test results for neat RAP aggregate give ACV, AIV, LAA, SG, MDD, and Water absorption of 11.4%, 9.2%, 10.2%, 2.41, 2.130, and 1.62% respectively. Also the mechanical blending of 30% RAP aggregate and 70% CRR test results were 15.9%, 13.8%, 16.6%, 2.230, 2.68 and 1.24% for ACV, AIV, LAA, MDD, SG, and Water absorption values respectively with 141KN and 170KN when soaked and dry in water for TFV results. The results obtained from Gradation, Atterberg’s limits, SG and water absorption ACV, AIV, LAA, and Compaction results indicate that Mixes containing 30% RAP contents were successfully replaced CRR in the road base course layer of Asphalt concrete.